2018
DOI: 10.1080/15548627.2018.1474993
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotubes, but not spherical nanoparticles, block autophagy by a shape-related targeting of lysosomes in murine macrophages

Abstract: Nanoparticles (NPs) can be toxic, depending on their physico-chemical characteristics. Macroautophagy/autophagy could represent a potential underlying mechanism of this toxicity. We therefore set up a study aimed to characterize in depth the effects, on autophagy, of macrophage exposure to NPs, with a particular attention paid to the role of NP physico-chemical characteristics (specifically chemical composition, shape, size, length, crystal phase, and/or surface properties). We demonstrate that exposure to car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 42 publications
3
25
0
Order By: Relevance
“…To further determine the changes in lysosome number, the level of Lamp1 was detected . The number of lysosomes increased to high levels after ZNPs treatment until 6 h, and similar results were observed after ZNPs treatment in the presence of EDTA, though EDTA alone had few effects on Lamp1 level (Figure G,H).…”
Section: Resultssupporting
confidence: 66%
“…To further determine the changes in lysosome number, the level of Lamp1 was detected . The number of lysosomes increased to high levels after ZNPs treatment until 6 h, and similar results were observed after ZNPs treatment in the presence of EDTA, though EDTA alone had few effects on Lamp1 level (Figure G,H).…”
Section: Resultssupporting
confidence: 66%
“…This is in contrast with other GBMs such as carbon nanotubes or GO, that have been shown to rather block the autophagic flux in RAW macrophages and peritoneal macrophages, respectively. 15,27 A very recent study, demonstrated that FLG at low doses could trigger autophagy in an ER-stress dependent manner and act as a protective mechanism in macrophages. 28 In our case, it is the first time that the impact of FLG on autophagy is focused on the major players of the adaptive immune response and as such, it could be interesting to study its impact on memory immune responses as well.…”
Section: Study Of Lymphocyte Autophagic Function In the Presence Of Flgmentioning
confidence: 99%
“…12 GO for instance appears to increase autophagy in macrophages, while carbon nanotubes induce a blockade of the autophagic flux as demonstrated in human umbilical vein endothelial cells and in macrophages. [13][14][15] Autophagy is also tightly linked to immune responses such as inflammatory responses, antigen presentation, pathogen clearance or lymphocyte homeostasis. 16 Since the immune system represents the first line of defense against any foreign element, we were interested in exploring the possible influence of FLG on autophagic functions of primary immune cells and in particular murine lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from its importance in physiological conditions, numerous studies have suggested that autophagy is regulated under different pathophysiological conditions, in particular in the lung brotic process (12,13). We have recently demonstrated that macrophagic autophagy can be modulated after exposure to NP, which could be of relevance in the context of pulmonary response to Ce exposure (14).…”
mentioning
confidence: 81%